Relación entre gastos de capital (CAPEX) y la tasa de crecimiento de ingresos de la empresa Cerveceria San Juan S.A, 2014 – 2022 - Hernández Orbe, Esteban André (2024)
This research analyzes the relationship between Capital Expenditure (CAPEX) and revenue growth at Cervecería San Juan S.A. during the period from 2014 to 2022. Employing a quantitative approach, robust statistical methods, including the Spearman correlation coefficient, were used to assess hypotheses suggesting a positive relationship between CAPEX and various financial metrics of the company. The general hypothesis proposed that there is a positive correlation between CAPEX and revenue growth, which was confirmed by a Spearman value of 0.3514 and a p-value of 0.046, indicating a moderately positive and statistically significant association. Additionally, two specific hypotheses were explored: the first indicated that the CAPEX-total revenue ratio positively correlates with revenue growth, validated with a coefficient of 0.3725 and a p-value of 0.038; the second suggested a positive relationship between the CAPEX-total revenue ratio and total revenues, corroborated by a coefficient of 0.1987 and a p-value of 0.043, albeit a weaker relationship. The results were contextualized with previous studies in different regions and sectors, highlighting a consistent pattern that underscores the importance of CAPEX in economic growth. This study contributes to the existing literature by providing empirical evidence on how capital investment strategies can influence the financial performance of companies.